Impact of Seasonal Generations of Dubas Bug Ommatissus binotatus on Oviposition and Chlorophyll in Three Date Palm Phoenix dactylifera L. Cultivars - Al-Saedi, Ghazwan Faisal; Al-Hamoud, Firas M.; Ali, Hazim M. (Basrah Journal Of Date Palm Research, 2025)
The study was conducted in the field in the Abu Al-Khasib area of Basrah Province, during the 2024 growing season to evaluate the impact of the dubas bug (Ommatissus binotatus) population density of spring and autumn generations on infestation rates, total chlorophyll concentration and oviposition in three date palms (Phoenix dactylifera L.) cultivars: Barhi, Sayer and Halawi. Infestation rates were highest in the during the two generations of dubas bug (Barhi cultivar 9.62%), (Sayer 8.17%), and Halawi (8.67%). This suggests that infestation rates significantly increased throughout the spring generation, particularly between March and June. As a result of a diminished insect impact at this time, infestation levels during the autumn generation were significantly lower or even nonexistent in certain months. Chlorophyll concentration varied between the two generations; higher values were generally observed during the autumn generation across most cultivars. The Sayer cultivar recorded the highest mean chlorophyll content, reaching 4.82 mg/g during the spring generation and 4.70 mg/g during the autumn, exceeding the levels recorded in Halawi and Barhi. Oviposition rates were also higher in the spring generation compared to the autumn. Barhi exhibited the highest average egg density with 0.61 eggs/cm² leaf area in the spring, slightly decreasing to 0.58 eggs/cm² in the autumn, with relatively stable values across the other cultivars. These findings indicate that the spring generation of O. binotatus exerts a greater adverse effect on date palm trees in terms of infestation and oviposition, while the autumn generation shows a comparatively milder impact. Insect density was shown to be negatively correlated with chlorophyll content and positively correlated with egg deposition. Differential susceptibility was demonstrated by the cultivars: Sayer had a comparatively higher level of resistance, whereas Barhi was the most sensitive. These findings highlight how crucial it is to include seasonal variation in integrated pest management (IPM) plans designed specifically for date palm production.